Large Scale Synthesis of Carbon Nanotubes - S. Karthikeyan; P. Mahalingam; M. Karthik (E-Journal of Chemistry)
Since the discovery of carbon nanotubes in 1991 by Iijima, they have been of great interest both from the fundamental point of view and for future applications. The most eye catching features of this structure are their electronic, mechanical, optical and chemical characteristics, which opens a way to future applications. These properties can even be measured on single nanotubes. For commercial applications, large quantities of purified nanotubes are needed. In this paper, recent research on preparation of carbon nanotubes with special reference to low temperature synthesis of high purity is reviewed. The reported achievements in this area will open up more knowledge on carbon nanostructured materials in many areas of emerging nanoscale science and nanotechnology